How Does Prosodic Prominence Impact Articulatory Movement Parameters and Movement Variability in Adults Who Stutter? - Kopera, Hailey C.; Grigos, Maria I. (Journal of Speech, Language & Hearing Research)
Purpose: This study examined how focus-induced changes in degree of prosodic prominence impact articulatory movement parameters and movement variability in adults who stutter (AWS) and adults who do not stutter (AWNS). AWS were predicted to display greater across-trial variability in closing and opening duration, displacement, and velocity compared to AWNS as prosodic demands (i.e., addition of pitch accent, degree of prosodic strengthening) increased. Method: Sixteen AWS and 15 AWNS participated in this study. A question--answer paradigm was used to manipulate the prosodic structure of spoken sentences through changes in semantic focus, and articulatory movement data were collected via a motion capture system. Kinematic analyses included oral closing and opening duration, displacement, and peak velocity, as well as the variability of these measures across repeated productions. Results: AWS and AWNS demonstrated prosodic strengthening of closing and opening gestures, contributing to the differentiation of non-focused and focused words, as well as different focus types (e.g., broad vs. narrow/contrastive). AWS demonstrated greater variability in closing displacement and velocity for unaccented, non-focused forms compared to other focus types and compared to AWNS, which was not in line with predictions. Conclusions: This work demonstrates a complex relationship between degree of prosodic prominence and articulatory movement variability. Based on patterns observed in AWS, but not AWNS, it is plausible that processes involved in suppressing default nuclear accents could act as linguistic stressors on the speech motor systems of AWS. Further research is needed to advance our understanding of the role of prosody within a multifactorial view of stuttering.